Efektifitas Pelaksanaan Program Pembinaan Narapidana Di Lapas Kelas II B Muara Sabak: Efektifitas pelaksanaan program pembinaan narapidana di lapas kelas II B Muara Sabak - vido valentino; Irwan; Sariani, Dona (Civic Education Perspective Journal, 2023)
PPKN (Citizenship Education) learning is learning related to applicable laws and regulations. abuse of narcoticsl isl a violationl of the lawl and there are articles that do not allow abuse of narcotics, it's just that people are indifferent to legislation and still violate a lot of predetermined norms. Class II B Narcotics Penitentiary (LAPAS) Muara Sabak as one of the government institutions that has the function of fostering convicts, especially convicts with cases of narcotics abuse, which continuesl to increasel everyl year. Thel purposel of this researchl isl to findl outl the coaching efforts carried out in Class II B Corrective Institution Of Muara Sabak In this study, the researcher used a qualitative research methodology with the aim of producing research in the form of elaborating words that presented the facts that had been obtained in the field. Data search techniquesl usedl are interviews,l observation,l and documentationl studies. Interviews were conducted with employees related to coaching. Froml thel resultsl of thisl studyl itl wasl foundl thatl thel Classl II B Narcoticsl Correctionall Institutionl in Muaral Sabak had a personality and independence development program. Personality development programs include religion, mentality and statehood. Meanwhile, self-reliance development programs include animal husbandry, agriculture and batik. These programs run well but have obstacles in their implementation, namely the number of inmates that exceed the capacity of LAPAS, facilities and infrastructure that are still lacking, the quality of coaching staff is not good, and the allocation of funding for program implementation is not optimal. Based on these findings it was concluded that the implementation of the coaching program at LAPAS Class II B Muara Sabak had not been running effectively as expected.